THE ENVIRONMENTAL DIMENSION OF SLUM UPGRADING - DENALDI,ROSANA (2018)
Abstract In metropolitan areas, a significant share of precarious settlements is located in environmentally protected areas. They have high levels of complexity and socio-environmental inequality compared with other areas of the overall territory. For this reason, any intervention in areas with such characteristics has to be managed by integrating social, urban and environmental dimensions. With regards to the evolution of slum upgrading policies and developments in the legal and institutional frameworks that regulate urban and environmental policies, the challenge to articulate these dimensions in order to guarantee both the right to housing and promote environmental recovery still remains. This paper is based on the theoretical panorama that problematizes the social production of space and divided approach to society and nature. It discusses the developments, limits and conflicts that emerge in the practice of slum upgrading. Two issues stand out: the management of the environmental dimension in upgrading projects and works; and the enforcement of the new regulatory frameworks to promote the regularization of these settlements.